PEMBERDAYAAN KADER KESEHATAN DAN KELUARGA DALAM PERAWATAN DAN PEMBERANTASAN PENYAKIT TB PARU - Anasril Anasril; Bustami Bustami; Tri Mulyono Herlambang (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. The main problems with TB today are the high prevalence rate and low compliance rate. In the village of Kuta Jeumpa, five new cases of pulmonary TB were found. Another problem is the lack of participation by health cadres in the prevention and eradication of pulmonary TB. This community service program aims to increase the capacity of health cadres and families of pulmonary TB patients in the treatment and eradication of pulmonary TB. The methods used are counseling, simulation, and training for PMO. The results of community service through education showed that the ability of cadres and families of pulmonary TB patients regarding efforts to prevent and eradicate pulmonary TB has increased. Families of pulmonary TB patients also have a better understanding of the role of PMO for pulmonary TB patients. These results indicate that follow-up is needed to improve efforts to prevent transmission and treat pulmonary TB by families, health centers, and other relevant agencies.